2014
DOI: 10.4235/jkgs.2014.18.4.213
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Geriatric Assessment for Elderly Orthopedic Inpatients Consulted by Geriatric Medicine in a Hospital

Abstract: Background: With a rapidly aging population, more elderly patients are being hospitalized than before. Thus, a comprehensive geriatric assessment medium is needed to carefully evaluate geriatric patients. The author's university hospital has a geriatric medicine team to where patients are referred for comprehensive evaluations. Their services will be introduced here. Methods: From December 2010 to January 2012, the team performed comprehensive geriatric assessments comprising of a thorough review of systems, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…It was observed that the use of HM increases with age. This finding was in line with other researchers (Kelly, Kaufman and Kelley, 2005; Hoist, Nordeng and Honvik 2008,Kim et al, 2003;…”
supporting
confidence: 93%
“…It was observed that the use of HM increases with age. This finding was in line with other researchers (Kelly, Kaufman and Kelley, 2005; Hoist, Nordeng and Honvik 2008,Kim et al, 2003;…”
supporting
confidence: 93%
“…Comprehensive Geriatric Assessment (CGA) is a multidimensional and interdisciplinary diagnostic process to determine the medical, psychological, and functional capabilities of older adults. CGA has been applied widely in many medical contexts including orthopedic 5) , coronary artery disease 6) , and multimorbidity. 7) Its purpose is tailored towards developing a coordinated and integrated plan for treatment and long-term follow-up.…”
Section: Introductionmentioning
confidence: 99%